ANALISIS EFISIENSI BISNIS KOMODITAS BUAH-BUAHAN DAN PERKEBUNAN UNGGULAN DI KABUPATEN BEKASI - Lutfiadi, Ridwan (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2010)
Bekasi area is quite appropriate for the development of fruit and plantation crops. But development is very slow to compete with similar commodities from other blood. Seeded fruit and plantation commodities in Bekasi is the mango, rambutan, banan, guava water and guava with the R/C respectively 1.92, 5.95, 1.98, 2:14, and 2.03. Similarly for plantation commodities are coconut, melinjo, and sengon efficiently with the R/C respectively;1.42; 3.16; and 3.16. The allocation of production factors for commodities of fruit and plantation almost all of them can still be improved and are on increasing returns to scale except the bananas are on the decreasing returns to scale.